POLICE USE OF TECHNOLOGY TO FIGHT AGAINST CRIME - Fatih, Tombul; Bekir, Cakar (European Scientific Journal, ESJ, 2015)
Traditionally, law enforcement agencies have had an unfriendly relationship with technology. However, there is no way one can ignore and/or resist the adoption of new technologies any longer since recent developments in information technology have changed the attitudes and perceptions of police forces as well as criminals. The technological advances over the years have provided law enforcement agencies new perspectives and considerations beyond the traditional methods and opportunities to utilize a wide range of innovations in different contexts. The recent innovations and implementations which increase the efficiency and effectiveness of policing including network analysis, GIS, crime mapping, biometrics, fingerprints, DNA research, facial recognition, speech recognition, social media policing, shotspotter detection system, and CCTV are detailed in this study.